PENGARUH SISTEM INFORMASI AKUNTANSI, PENGENDALIAN INTERNAL DAN PEMANFAATAN TEKNOLOGI INFORMASI TERHADAP KUALITAS LAPORAN KEUANGAN PADA PT. PUPUK SRIWIDJAJA PALEMBANG - Azwari, Peny Cahaya; Syaputri, Regita Damayanti; Jayanti, Sri Delasmi; Nuraliati, Ayke Nuraliati (Balance : Jurnal Akuntansi dan Bisnis, 2024)
This study, titled "The Influence of Accounting Information Systems, Internal Control, and Utilization of Information Technology on the Quality of Financial Reports at PT. Pupuk Sriwidjaja Palembang", uses a quantitative method, with data sources obtained from primary data. This research data was collected through distributing questionnaires directly to employees. The population in this study were all employees of PT. Pupuk Sriwidjaja Palembang. The samples were taken using purposive sampling, so the number of samples in this study was 75 PT employees. Pupuk Sriwidjaja Palembang. The data analysis techniques used in this study include outer model testing, inner model testing, and hypothesis testing using Structural Equation Modeling (SmartPLS SEM) version 4 software. The results of the study show that, partially, accounting information systems have a positive and significant effect on the quality of financial reports, internal control has a positive and significant effect on the quality of financial reports, and the utilization of information technology has a positive and significant effect on the quality of financial reports.